Brosco-Dutka classification system for palate fistulas - Telma Vidotto de Sousa Brosco; Gabriela Aparecida Prearo; Hagner Lucio de Andrade Silva; Jeniffer De Cassia Rillo Dutka (Revista Brasileira de Cirurgia Plástica)
Introduction: The occurrence of post-palatoplasty oronasal fistula (ONF) is undesirable, challenging and difficult to classify complications. The objective is to present a classification protocol for palate fistula based on the fistula's morphological, embryological criteria and symptomatology. Methods: The elaboration of the classification involved the following steps: definition of ONF; definition of anatomical references; establishment of embryological and morphological criteria; inclusion of symptomatology. Discussion: The established protocol includes strategies for identifying anatomical references of complex visualization such as foramen (FI) and the transition area between the hard and soft palate. From the point of view of embryology, the fistula can be classified as PREFI (located in the region before the FI), POSFI (located in the region after the FI) and PREPO (which affects both the region before and after the FI). The morphological criterion establishes as areas: region-1: prealveolar and/or the alveolar arch; region-2: hard palate before FI; region-3: hard palate after FI; region-4: transition between hard and soft palate; and region-5: soft palate. Symptom identification includes hypernasality, ear infections and nasal reflux, in addition to asymptomatic fistulas. Obtaining adequate intraoral photographs facilitates the protocol's applicability, and the positioning for the photographic image requires the visualization of the palatal face of the upper incisor teeth. Conclusion: The Brosco-Dutka protocol for the classification of palate fistula was developed for use by the craniofacial team during a face-to-face consultation or photographic image analysis. The proposal presents illustrations to guide the proper use of the criteria.